62.2k views
3 votes
In order to solve for the variable in the equation 2 (x + 3) + 5 x = 3 (2 x minus 1), Jaleesa begins by applying the distributive property, then combines like terms. Which equation is the result of these steps?

7 x + 6 = 6 x minus 3
2 x + 6 + 5 x = 6 x minus 3
2 x + 3 + 5 x = 6 x minus 1
7 x + 3 = 6 x minus 1

User Scaryzet
by
5.2k points

2 Answers

3 votes

Answer:7x+6=6x-3

Explanation:

In order to solve for the variable in the equation 2 (x + 3) + 5 x = 3 (2 x minus-example-1
User Morgana
by
4.5k points
6 votes

Answer: 7 x + 6 = 6 x minus 3

Explanation:

  1. 2 (x + 3) + 5 x = 3 (2 x minus 1)
  2. Now you distribute.
  3. 2(x) + 2(3) = 2x+6
  4. And 3(2x) minus 3(1) = 6x minus 3
  5. 2x+6+5x = 6x minus 3
  6. Then combine like terms
  7. 2x +5x=7x and there are no other like terms on either side of the equation.
  8. 7x+6= 6x minus 3

User Rim
by
5.3k points